2018
DOI: 10.1103/physrevlett.121.058102
|View full text |Cite
|
Sign up to set email alerts
|

Width Scaling of an Interface Constrained by a Membrane

Abstract: We investigate the shape of a growing interface in the presence of an impenetrable moving membrane. The two distinct geometrical arrangements of the interface and membrane, obtained by placing the membrane behind or ahead of the interface, are not symmetrically related. On the basis of numerical results and an exact calculation, we argue that these two arrangements represent two distinct universality classes for interfacial growth: while the well-established Kardar-Parisi-Zhang (KPZ) growth is obtained in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…We define B as a κ-independent constant. We repeat this method to extract the κ-dependence from the (N − 1)dimensional integrals in (9) to give an overall scaling for the membrane velocity…”
Section: Velocity Scaling Lawmentioning
confidence: 99%
See 2 more Smart Citations
“…We define B as a κ-independent constant. We repeat this method to extract the κ-dependence from the (N − 1)dimensional integrals in (9) to give an overall scaling for the membrane velocity…”
Section: Velocity Scaling Lawmentioning
confidence: 99%
“…In mathematical terms, the standard Brownian ratchet may be formulated as a drift-diffusive problem for a single spatial co-ordinate [5]. More recently many-filament systems involving several spatial co-ordinates have been introduced and studied [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, membrane fluctuations have not yet been studied. In most studies reported in the literature [16][17][18][19][20][21][22][23], the membrane is modeled as a flat rigid surface; thus, no fluctuations are accounted for. Although the membrane fluctuations are assumed to be a Gaussian distribution of the membrane height in Ref.…”
mentioning
confidence: 99%
“…For example, actin filaments grow at the front side of crawling cells and push the membrane forward. This membrane motion has been intensively studied by Brownian ratchet theories and simulations [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
mentioning
confidence: 99%